2009
DOI: 10.1073/pnas.0812715106
|View full text |Cite
|
Sign up to set email alerts
|

The mismatch repair system promotes DNA polymerase ζ-dependent translesion synthesis in yeast

Abstract: DNA lesions that block replication can be bypassed by error-prone or error-free mechanisms. Error-prone mechanisms rely on specialized translesion synthesis (TLS) DNA polymerases that directly replicate over the lesion, whereas error-free pathways use an undamaged duplex as a template for lesion bypass. In the yeast Saccharomyces cerevisiae, most mutagenic TLS of spontaneous and induced DNA damage relies on DNA polymerase (Pol ) activity. Here, we use a distinct mutational signature produced by Pol in a frames… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
4
22
0
Order By: Relevance
“…Maximal expression of Rev1 outside of S phase has led to the suggestion that most Pol z-dependent lesion bypass occurs via gap-filling reactions that occur well behind the replication fork. Consistent with this, spontaneous, Pol z-dependent lesion bypass is refractory to correction by the MMR machinery (Lehner and Jinks-Robertson 2009). The higher mutation rate of late-replicating DNA also is reduced in rev1D background (Lang and Murray 2011), consistent with the cell-cycle regulation of Rev1 and suggesting that there may be temporal separation of error-free and error-prone lesion bypass.…”
Section: When and Where Does Prr Occur?mentioning
confidence: 66%
“…Maximal expression of Rev1 outside of S phase has led to the suggestion that most Pol z-dependent lesion bypass occurs via gap-filling reactions that occur well behind the replication fork. Consistent with this, spontaneous, Pol z-dependent lesion bypass is refractory to correction by the MMR machinery (Lehner and Jinks-Robertson 2009). The higher mutation rate of late-replicating DNA also is reduced in rev1D background (Lang and Murray 2011), consistent with the cell-cycle regulation of Rev1 and suggesting that there may be temporal separation of error-free and error-prone lesion bypass.…”
Section: When and Where Does Prr Occur?mentioning
confidence: 66%
“…With regard to the former possibility, we previously reported that suppression of recombination by the MMR system promotes Polz-dependent mutagenesis via the alternative translesion synthesis pathway, making such mutations dependent on functional MMR (Lehner and Jinks-Robertson 2009). We thus examined whether small duplications depend on the presence of Polz.…”
Section: Removal Of 1-bp Deletion Intermediates By the Mmr Machinerymentioning
confidence: 99%
“…lys2ΔA746NR, lys2ΔA746NR,(AT) 2, or lys2ΔA746NR,(TC) 3 derivatives were constructed by two-step allele replacement by using AflIIdigested pSR963 (17), pSR1002, or pSR1003, respectively. pSR1002 and pSR1003 were derived by annealing oligonucleotides [5′-gatcGGTTTTGC-CACATATCTTCAACGCTG and 5′-gatcCAGCGTTGAAGATATGTGGCAAAACC for the (AT) 2 hotspot or 5′-gatcATACCGTGGCATCTCTCGTGACGAGTTAC and 5′-gatcGTAACTCGTCACGAGAGATGCCACGGTAT for the (TC) 3 hotspot; hotspots are underlined, and BglII-compatible overhangs are in lowercase] and then inserting the resulting ≈30 bp fragments into BglII-digested pSR963.…”
mentioning
confidence: 99%